DAKWAH PENANAMAN NILAI-NILAI KARAKTER DAN RELEVANSINYA TERHADAP PENANGKALAN RADIKALISME PADA KALANGAN SANTRI DI KABUPATEN ACEH JAYA - Paisal, Jon; Mukhlizar (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
In this technological era, it is effortless to be exposed to radicalism and terrorism. Moreover, Aceh, a former conflict area, is considered very worthy of being declared violent by certain groups. Moreover, this understanding will enter the dayah environment, affecting the students. The research entitled Da'wah is about cultivating character values ​​and their relevance to preventing radicalism among students in Aceh Jaya Regency. Using qualitative research methods, data were collected through interviews, documentation and observations in several dayahs in Aceh Jaya District. The study results reveal that the views of the dayah ulama in Aceh Jaya reject radicalism and terrorism. To prevent the exposure of radicalism among the santri, the dayah ulama in Aceh Jaya district carried out da'wah to instill character values ​​in students through the exemplary attitude of the dayah ulama. Encourage students to get used to memorizing the Qur'an and recitation of the yellow book. Moreover, the cultivation of character values ​​through activities to commemorate significant holidays.